Screening for human trafficking among refugees in Germany [data and analysis]: determining prevalence and test accuracy of a modified version of the adult human trafficking screening tool - Tambini Stollwerck, Estella; Dönnhoff, Ivo; Friederich, Hans-Christoph; Nikendei, Christoph (Universität, 2023)
Background: Human trafficking occurs all over the world and its true extent is still unknown. What we know is that the actual number of trafficked persons is significantly higher than the number of registered cases in Europe or anywhere else. Human trafficking is particularly likely among refugees, as they easily fall for false promises due to language barriers, lack of knowledge on the local culture and difficult living conditions. Therefore, the purpose of this study was to create a screening tool to identify survivors of human trafficking among refugees in a German state registration and reception centre. Method: In a joint project with the Ministry of Justice of Baden-Württemberg and the Regional Administrative Authority of Karlsruhe (“Regierungspräsidium”), we asked new arrivals at the initial reception centre in Heidelberg on a weekly basis from December 2021 to June 2022 about their experiences with human trafficking. We used a combination of the eight questions of the Adult Human Trafficking Screening Tool and one screening question borrowed from a publication by Mumma et al. to address all forms of exploitation. If trafficking indeed was the case, was validated by face-to-face contacts with forced migrants screened positive. Results: Overall, 13 of the 176 asylum seekers had experienced trafficking, which corresponded to a prevalence of 7.3%. The dichotomous questionnaire had a sensitivity of 76.9% and a specificity of 84.0% at a newly selected cut-off of six positive responses. In an exploratory descriptive analysis on subregions, refugees from West Africa had a substantially higher prevalence (33.3%) for trafficking in human beings within our sample and in this subgroup, mainly female refugees were affected by trafficking. In comparison, there were hardly any gender differences in the represented parts of the rest of the world in our study. Conclusion: The modified form of the AHTST distinguishes reliably those who had experienced human trafficking from other refugees. The high prevalence of trafficking in most regions, regardless of gender, suggests that more effort is needed to identify and protect trafficked persons. (2023)